Pengaruh Model Pembelajaran Saintifik pada Kurikulum 2013 dan Kompetensi Profesional Guru terhadap Hasil Belajar Siswa Kelas VIII di MTSN 2 Bogor - Lisnamayanti Lisnamayanti; Imam Tholkhah; Amie Primarni (Jurnal Dirosah Islamiyah, 2020)
This study discusses "The Effect of the Scientific Learning Model on the 2013 Curriculum and Teacher Professional Competence on Student Learning Outcomes of Class VIII at MTsN Bogor. The purpose of this study is to find out whether there is a significant influence between the Scientific Learning Model in the 2013 curriculum and Teacher Competence Against Results Learning grade VIII students of MTsN 2 Bogor. This study uses a Quantitative Method in which the researcher processes the data with questionnaire distribution questionnaire technique with a Likert scale of variables X 1 (Scientific learning model in the 2013 curriculum) and X2 (Teacher Professional Competence) and Y (Student Learning Outcomes of Class VIII) given to students from the population of students in class VIII a total of 380, then a sample of 15% was taken in a total of 60 students. From the results of this study the significant value of the effect of X1 on Y is 0.996> 0.05 and the count-0.005 <ttable2.00247, so it can be stated that the scientific learning model in the 2013 curriculum (X1) can be accepted in other words there is the influence of the scientific learning model in the 2013 curriculum on the learning outcomes of students of class VIII at MTsN 2 Bogor. While the significant value of X2 against Y with a value of 0.162> 0.05 and the value of 1.415 <ttable2.00247, it can be concluded that X2 is accepted in other words there is no effect of teacher professional competence on student learning outcomes at MTsN 2 Bogor. That the significant value for the effect of X1 and X2 simultaneously on Y is 0.291 <0.05 and the value of Fcount is 1.263 <Ftable 3.16 so that it can be stated that X1 and X2 have no effect on Y. Significant value for the influence of X1 and X2 simultaneously to Y is 0.291> 0.05 and the value of Fcount is 1.263 <Ftable 3.16 so that it can be stated that X1 and X2 have an influence on Y. In the coefficient of determination the R square value of 0.42 this implies that the influence of variables X1 and X2 on Y by 42%. Keywords: learning model, curriculum, teacher competency, students